2009
DOI: 10.1093/eurheartj/ehp122
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-rich plaque and myocardial perfusion after successful stenting in patients with non-ST-segment elevation acute coronary syndrome: an optical coherence tomography study

Abstract: Optical coherence tomography can predict no-reflow after percutaneous coronary intervention (PCI) in NSTEACS. The lipid contents of a culprit plaque may play a key role in damage to the microcirculation after PCI for NSTEACS. From our results, it is found that OCT is useful tool for stratifying risk for PCI for NSTEACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(93 citation statements)
references
References 36 publications
2
88
0
3
Order By: Relevance
“…1,17,23 In addition, OCT can identify TCFA by measuring the thickness of the fibrous cap and the arc of the lipid-rich plaque. [24][25][26] Lipid pools are less sharply delineated than calcification and show lower signal intensity. Lipids also exhibit more heterogeneous backscattering than fibrous plaques.…”
Section: Plaque Characterisationmentioning
confidence: 99%
See 3 more Smart Citations
“…1,17,23 In addition, OCT can identify TCFA by measuring the thickness of the fibrous cap and the arc of the lipid-rich plaque. [24][25][26] Lipid pools are less sharply delineated than calcification and show lower signal intensity. Lipids also exhibit more heterogeneous backscattering than fibrous plaques.…”
Section: Plaque Characterisationmentioning
confidence: 99%
“…25,26,30 OCT images for white thrombi (composed of platelets and leucocytes) produce a signal-rich mass whereas red thrombi (containing mainly erythrocytes) produce high backscattering protrusions with strong signal attenuation. 31 If there is a large red thrombus, then this may interrupt the visualisation of the characteristics of an underlying plaque due to signal attenuation.…”
Section: Thrombusmentioning
confidence: 99%
See 2 more Smart Citations
“…Tanaka et al showed that TCFA was often observed at target lesions of the patients with no reflow after PCI compared with good reflow (50% versus 16%, P = 0.005). The frequency of the no reflow phenomenon increased according to the lipid arc assessed by OCT [11]. When OCT detects lipid-rich plaque and TCFA especially in patients with ACS, we should consider to use distal protection devices to prevent no-reflow phenomenon.…”
Section: Clinical Applications Of Oct Imagingmentioning
confidence: 99%